2017
DOI: 10.1080/15384101.2017.1367073
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling conflicting models for global control of cell-cycle transcription

Abstract: Models for the control of global cell-cycle transcription have advanced from a CDK-APC/C oscillator, a transcription factor (TF) network, to coupled CDK-APC/C and TF networks. Nonetheless, current models were challenged by a recent study that concluded that the cell-cycle transcriptional program is primarily controlled by a CDK-APC/C oscillator in budding yeast. Here we report an analysis of the transcriptome dynamics in cyclin mutant cells that were not queried in the previous study. We find that B-cyclin osc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 78 publications
(214 reference statements)
2
23
0
Order By: Relevance
“…Cell cycle-arrested budding yeast lacking multiple mitotic and S-phase cyclins continued to show periodic activation of subsequent G1-specific events that were essential for cell-cycle progression (Haase and Reed, 1999). Comprehensive microarray studies of budding yeast in aerobic continuous culture revealed that more than half of genes in the budding yeast genome are expressed periodically, in accordance with respiratory oscillations (Spellman et al, 1998; Klevecz et al, 2004; Tu et al, 2005; Cho et al, 2017) and with cell-cycle progression (Cho et al, 1998; Spellman et al, 1998; Klevecz et al, 2004; Tu et al, 2005). These results are consistent with a model in which genome-wide transcriptional oscillation is independent of the CDK oscillator and coupled with other oscillators.…”
Section: Building a Unified Model Of The Quantitative Studies For Celmentioning
confidence: 99%
“…Cell cycle-arrested budding yeast lacking multiple mitotic and S-phase cyclins continued to show periodic activation of subsequent G1-specific events that were essential for cell-cycle progression (Haase and Reed, 1999). Comprehensive microarray studies of budding yeast in aerobic continuous culture revealed that more than half of genes in the budding yeast genome are expressed periodically, in accordance with respiratory oscillations (Spellman et al, 1998; Klevecz et al, 2004; Tu et al, 2005; Cho et al, 2017) and with cell-cycle progression (Cho et al, 1998; Spellman et al, 1998; Klevecz et al, 2004; Tu et al, 2005). These results are consistent with a model in which genome-wide transcriptional oscillation is independent of the CDK oscillator and coupled with other oscillators.…”
Section: Building a Unified Model Of The Quantitative Studies For Celmentioning
confidence: 99%
“…Of these, ChIP, Deletion, and PWM1 have significantly fewer TF-target interactions with each other than expected categories by Spellman et al [63]. Although multiple transcriptome studies of the yeast cell cycle have been characterized since, we use the Spellman et al definition because it provides a clear distinction between the phases of the cell cycles which remains in common use [10,12,21,28,51,54,59,60]. The Spellman definition of cell-cycle genes includes five phases of expression, G1, S, S/G2, G2/M, and M/G1, consisting of 71-300 genes based on the timing of peak expression that corresponds to different cell cycle phases ( Fig.…”
Section: Recovering Phase-specific Expression During S Cerevisiae Cementioning
confidence: 99%
“…1, center). 2 Tests of these models have aimed to block oscillations in CDK activity and cell-cycle progression by holding cells at either low CDK activity 3,4 or high CDK activity 5,6 , followed by examining the effects on cell cycle transcription. Surprisingly, blocks at either low or high CDK activity failed to impede certain transcriptional oscillations, and demonstrated that much of the periodic transcriptional program could be uncoupled from cell-cycle progression.…”
mentioning
confidence: 99%
“…To address this contradiction directly, Cho et al analyzed data published by both groups. 6 Even with distinctions in experimental approach and variations in the engineered yeast strains, the two groups provide remarkably reproducible and complementary data. While it is tempting to speculate that subtle variations appeared due to differences in strains, experimental protocol, or quantitative analysis, Cho et al provide compelling explanations for variations and provide a new set of experimental evidence underscoring a model in which CDKs are part of a transcriptional oscillator, but that periodic input from CDK is not required to drive global transcriptional oscillations.…”
mentioning
confidence: 99%
See 1 more Smart Citation